An adapted two-step floating catchment area method accounting for urban–rural differences in spatial access to pharmacies - Zhou, Yuhong (J Pharm Health Serv Res, 2021)
OBJECTIVE: To adapt the two-step floating catchment area approach to account for urban–rural differences in pharmacy access in the United States. METHODS: The urban–rural two-step floating catchment area method was described mathematically. To calculate urban–rural-two-step floating catchment area measure, census tracts and pharmacies within the study area (Southeastern Wisconsin) were classified as urban, suburban or rural, and then different catchment area sizes (2, 5 and 15 miles) were applied, based on the Centers for Medicare & Medicaid Services (CMS)’ criteria for Medicare Part D service access within urban, suburban and rural areas. The urban–rural-two-step floating catchment area measures were compared to traditional two-step floating catchment area measures computed using three fixed catchment area sizes (2, 5, and 15 miles) by visually examining their spatial distributions. Associations between the four pharmacy accessibility measures and selected socio-demographics are calculated using Spearman’s rank-order correlation and further compared. KEY FINDINGS: The urban–rural two-step floating catchment area measure outperforms all the fixed catchment size measures and has the strongest Spearman correlations with the selected census variables. It also reduces the number of census tracts characterized as ‘no access’ when compared to the original measures. The spatial distribution of urban–rural two-step floating catchment area pharmacy access exhibits a more granular variation across the study area. CONCLUSIONS: The results support our hypothesis that spatial access to pharmacies should account for urbanicity/rurality patterns within a region.